A Business Model-LCA of air purifiers Comparing sales and rental business model in Sweden - Norin, Albert; Reenbom, Erik (My University, 2024)
This study investigates the potential of decoupling economic growth from environmental impact through innovative business models, using the case of an air purifier company. The company is exploring a rental model as an alternative to traditional sales, aiming to enhance sustainability by ensuring product longevity, increased recycling, and efficient resource use. The study compared the environmental performance of these two models using the Business Model Life Cycle Assessment (BM-LCA) methodology, which connects profitability with environmental impact. Results showed that the rental model has a lower impact normalized per amount of generated profit, when compared to the sales model in almost all impact categories. For instance, there is a potential reduction of 10% for the rental compared to the sales model for the climate change impact. Also, the contribution of the air purifier’s life cycle stages to various impact categories differs between the models. The product assembly has the larger contribution to almost all impact categories for the sales model, while for the rental model the filter assembly become more relevant. The reason for this is that the different models require different flows of air purifiers and filters to achieve the same profit margin. A sensitivity analysis showed that a change of energy mix would have a large influence on the results, increasing the importance of energy efficiency measures if the rental service would expand into other markets than Sweden. The analysis also identified the subscription fee and technical lifetime of the purifier as factors that could influence the impact of the results. To conclude, the study showed that a rental model can have an overall better environmental performance than a sales model while still providing the same profit for the company. Analysis based on the results revealed that the geographical location of the service, technical lifetime and subscription fee had great impact on the overall environmental impact. Recommended future work for the company would be to improve the lifetime of the filters, since they are the biggest contributing process to the environmental impact over time. The calculation model created for the comparison of the business models, can be used for an expanded sensitivity analysis where more parameters can be studied, e.g., the filter replacement rate or broadening the scope, assessing other markets outside of Sweden.
Keywords: BM-LCA; Life cycle assessment; circular business models; consumption; sharing economy; product service system; environmental assessment of business models